Raw Material Inventory Control Analysis Of Shuttletcock PT. Walet putih - Astuti, Tri; Kurniawan, Rony (Proceeding Kilisuci International Conference on Economic & Business, 2025)
Research aim : This study aims to analyze the most dominant factors in the number of efficient Shuttlecock raw material orders in order to fulfill the raw material inventory at PT. Walet Putih and determine the Safety Stock and Re-Order Point. Design/Methode/Approach : In this study the method used is quantitative descriptive and the calculation model used isEconomic Order Quantity (EOQ).The subject of this study is the supply of Shuttlecock raw materials. Data collection techniques are carried out using interviews and documentation. Research Finding : The results of this study indicate that the purchase of Shuttlecock raw materials obtained an economic order quantity or can be called the Economic Order Quantity (EOQ) of 1,329 dozens per order. The maximum inventory level based on the average maximum value of 664 dozens. This value is the safety stock value based on the average inventory of 1,692 dozens or the amount of safety stock is 1,028 dozens greater than the company's calculation. The Re-Order Point value is 1,791 dozens. While the Total Cost (TC) value generated is 2,517,849,000 every 12 months. This value is the total sum of the total Inventory (Holding + Set Up) Cost. This value is usually greater than the amount that can be spent Rp. 183,348,800. Or a difference of more than Rp. 2,334,500,200. Theoretical contribution/Originality : The results of this study are expected to be useful and to increase understanding of operational management, especially in raw material inventory using the calculation method with Economic Order Quantity (EOQ). Practitionel/Policy implication : For business people, the results of this study are expected to be applied in their companies to overcome current problems, namely shortages and excesses of raw material supplies Research limitation : The limitation of this study is that the data comes from historical data, so it cannot describe the actual conditions because the condition of raw material inventory can change over time.